Mastication stimuli regulate the heartbeat rate through rhythmic regulation by the hypothalamic-autonomic system; molecular and telemetric studies in weaning-stage rats - Lee, Seonmi; Tochinai, Ryota; Yasuoka, Akihito; Nagai, Toshitada; Saito, Yoshikazu; Kuwahara, Masayoshi; Abe, Keiko; Asakura, Tomiko (Frontiers in Neuroscience, 2023)
Mastication stimuli have been demonstrated to affect memory function and autonomic nerve activity; however, this process has not been well studied during weaning compared to old age. Previously, we conducted molecular analyses of the thalamus and hippocampus to elucidate the mechanisms underlying this memory-enhancing effect in weaning-stage rats. In this study, we aimed to evaluate the effect of masticatory stimuli on the regulation of heartbeat rate (HR) through the hypothalamic-autonomic system. Three-week-old male rats were administered a powdered diet (P group) or chow-diet (C group) for 10 days. Thereafter, transcriptome analysis was performed. Vasopressin, cocaine-amphetamine-regulated transcript prepropeptide, corticotropin-releasing hormone, and thyrotropin-releasing hormone, which are involved in sympathetic activation of heart rate, were downregulated in the C group. Electrocardiograms were recorded continuously for 12 days under the same condition. Interestingly, rats in the C group had a significantly lower HR than those in the P group on day 11. We checked several parameters representing the autonomic regulation of HR. The C group had higher values for the high-frequency band integration of the HR power spectrum (parasympathetic marker) and root mean square successive difference of R-wave intervals (parasympathetic marker) relative to the P group. Such findings provide a molecular and physiological basis for understanding the regulation of cardiovascular function in response to masticatory stimuli in the autonomic nervous system.